EMOTIONAL INTELLIGENCE AS THE MAIN COMPETENCE OF PERSONALITY - V. Furman (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article contains theoretical provisions for understanding of the phenomenon of emotional intelligence as metacompetence of personality. It is examined the content of the concept of "emotional intelligence" and its structure. The article scientifically confirms the need to develop emotional intelligence as the basis for a successful personality self-identity. Analysis of the current research shows that great attention to the problem of emotional intelligence emerged in the last decade. The driving force is the employers, large companies that require versatile professionals and investe in the development of empathy in the staff that focus on intellectual capital personality. Emotional intelligence is the main component in achieving maximum successful fulfillment. It is an essential factor motivating mental activity as recognition of the feelings and manage them in a constructive way to increase the intellectual power of personality. To raise the level of emotional intelligence is completely possible due to the training, personal motivation, a desire to change himself, to get out of the comfort zone of personality - it is an important step to increase the level of emotional intelligence which leads to self-improvement.